Glomerulonephritis to Renal Cell Carcinoma: Diagnostic Dilemma with Successful Management of a 8 Year Old Boy - Quader, Mohammed Maruf Ul; Muhuri, Basana Rani; Karim, AKM Rezaul; Sultana, Sharmin; Hoque, Sayed Mesbahul (Bangladesh Journal of Child Health, 2017)
Abstract not available Bangladesh J Child Health 2016; VOL 40 (3) :186-188